Effects of Recycled Aggregate Resin (RAR) in Concrete Material - Sharifah Salwa Mohd Zuki; Shahidan, Shahiron; Subramaniam, Shivaraj (International Journal of Sustainable Construction Engineering and Technology, 2020)
This paper discussed the recycled aggregates produced from construction and demolition waste and their utilization in concrete construction. Along with a brief overview of the engineering properties of recycled aggregates, the paper also summarizes the effect and use of recycled aggregates on the properties of fresh and hardened concrete. The recycled aggregates were treated with epoxy resin to reduce the water absorptions with different percentages of resin such as 0%, 25%, 50%, 75%, and 100%. Epoxy resin is widely used in recent years owing to the enhancing of mechanical and durability of the concrete. This research also showed, recycled aggregate concrete are close proximity to normal concrete in terms of split tensile strength, compression strength and wet density. The low usage of resin was obtained good strength concrete compared to high percentage contained treated aggregates due to low bonding between material.